2015
DOI: 10.1016/j.ijsolstr.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hysteresis and temperature on magnetoelectric effect in giant magnetostrictive/piezoelectric composites

Abstract: a b s t r a c tA nonlinear dynamic hysteretic theoretical model on magnetoelectric effect of tri-layered composites is built based on a nonlinear constitutive relation for magnetostrictive material and a linear piezoelectric model for piezoelectric material. And a finite element analysis is implemented to investigate quantitatively the influences of hysteresis and temperature on the ME effect of the layered composites. The model also can explain the ''self-biased'' response caused by the hysteretic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…In particular this study relies on the following peculiar experimental findings on, even different, ME composites for tuning the ME coupling coefficient: a) the hysteresis loop of ME composites can be leveraged to induce the ME effect even when the DC magnetic field, which is used to magnetize them, is removed ("self-biased" ME composites) [24][25][26]. As a consequence, different core materials, with different hysteretic properties, differently affect the ME coefficient; b) core volume and surface shell thickness, as well as their relative dimensions, [14,18,19,27,28] play a crucial role in all the phases of magnetoelectric process (i.e.…”
Section: Plos Onementioning
confidence: 99%
“…In particular this study relies on the following peculiar experimental findings on, even different, ME composites for tuning the ME coupling coefficient: a) the hysteresis loop of ME composites can be leveraged to induce the ME effect even when the DC magnetic field, which is used to magnetize them, is removed ("self-biased" ME composites) [24][25][26]. As a consequence, different core materials, with different hysteretic properties, differently affect the ME coefficient; b) core volume and surface shell thickness, as well as their relative dimensions, [14,18,19,27,28] play a crucial role in all the phases of magnetoelectric process (i.e.…”
Section: Plos Onementioning
confidence: 99%
“…Some representative works are carried out [32][33][34]. For example, Zhang & Gao [32] established a nonlinear dynamic hysteretic model for giant magnetostrictive/piezoelectric composites, and implemented a finiteelement analysis to investigate the influences of hysteresis and temperature on the ME effects of M/P/M and P/M/P structures (M: magnetic; P: piezoelectric). Combining a nonlinear hysteretic magnetostrictive model and a structural vibration theory, Xu et al [33] studied the frequency dependence of the harmonic hysteretic ME effect in a multiferroic composite.…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, some theoretical studies have started to emerge. Some representative works are carried out [32][33][34]. For example, Zhang & Gao [32] established a nonlinear dynamic hysteretic model for giant magnetostrictive/piezoelectric composites, and implemented a finiteelement analysis to investigate the influences of hysteresis and temperature on the ME effects of M/P/M and P/M/P structures (M: magnetic; P: piezoelectric).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many FM materials (e.g., Terfenol-D and Ni) present complex multi-field coupling characteristics, which have a significant impact on the ME response of ME composites under combined stress, magnetic and thermal loadings. Previous work conducted on bulk ME composites showed that the interplay of these external fields makes the optimal design of ME devices more complicated [24,25,26,27,28,29]. As for the multiferroic composites with nano-scale thickness, the applied external stimuli (e.g., magnetic field, pre-stress and temperature) influence the magnetostriction and magnetization of FM phase, so they may have effects on strain gradient as well as the materials’ properties of FM materials.…”
Section: Introductionmentioning
confidence: 99%